Advanced Maternal Age Worsens Postpartum Vascular Function - Morton, Jude S.; Care, Alison S.; Kirschenman, Raven; Cooke, Christy-Lynn; Davidge, Sandra T. (Frontiers in Physiology, 2017)
The age at which women experience their first pregnancy has increased throughout the decades. Pregnancy has an important influence on maternal short- and long-term cardiovascular outcomes. Pregnancy at an advanced maternal age increases maternal risk of gestational diabetes, preeclampsia, placenta previa and caesarian delivery; complications which predict worsened cardiovascular health in later years. Aging also independently increases the risk of cardiovascular disease; therefore, combined risk in women of advanced maternal age may lead to detrimental cardiovascular outcomes later in life. We hypothesized that pregnancy at an advanced maternal age would lead to postpartum vascular dysfunction. We used a reproductively aged rat model to investigate vascular function in never pregnant (virgin), previously pregnant (postpartum) and previously mated but never delivered (nulliparous) rats at approximately 13.5 months of age (three months postpartum or equivalent). Nulliparous rats, in which pregnancy was spontaneously lost, demonstrated significantly reduced aortic relaxation responses (methylcholine [MCh] Emax: 54.2±12.6%) vs. virgin and postpartum rats (MCh Emax: 84.8±3.5% and 84.7±3.2% respectively); suggesting pregnancy loss causes a worsened vascular pathology. Oxidized LDL reduced relaxation to MCh in aorta from virgin and postpartum, but not nulliparous rats, with an increased contribution of the LOX-1 receptor in the postpartum group. Further, in mesenteric arteries from postpartum rats, endothelium-derived hyperpolarization (EDH)-mediated vasodilation was reduced and a constrictive prostaglandin effect was apparent. In conclusion, aged postpartum rats exhibited vascular dysfunction, while rats which had pregnancy loss demonstrated a distinct vascular pathology. These data demonstrate mechanisms which may lead to worsened outcomes at an advanced maternal age; including early pregnancy loss and later life cardiovascular dysfunction.